Middle-class youth fleeing Nigeria: rethinking African survival migration through the Japa phenomenon - Liu, Jing Jing (Journal of ethnic and migration studies, 2024)
Migration for survival is commonly associated with refugees and asylum seekers who flee persecution, wars, and natural calamities. Yet, in Nigeria, university-educated, gainfully employed middle-class youth insist that leaving is a matter of survival and not a choice. This distinction is signalled by japa, a recently popularised term for 'to run' or 'to flee'. Young Nigerians view migration as an escape from intolerable domestic conditions - prolonged university strikes, overturned development progress, and unprecedented currency inflation. In practice, japa follows formal procedures but favours quick departures. But by framing migration as fleeing, youth emphasise their refusal to cope. Foremost, they emphasise urgent respite over rationalised projects of social reproduction or status maintenance. Scholars, however, tend to overlook emotional or existential motives for voluntary migration and essentialise survival drives to forced migration. Drawing on 21 interviews with Nigerian youths, this paper shows a need to rethink survival migration, particularly how we value destinations compared to departures, conflate urgent desires with immediate exits, and privilege social functions over individual sentiments. By analysing youth's interpretations of what survival means, we enrich our understanding of African migration beyond the binary of elite strategies for social reproduction or fateful journeys of forced migration.